X-ray absorption spectroscopy identification of Mn-doped Bi 3.25La0.75Ti3O12 ceramics - Kanokwan Kanchiang (2018)
In this work, x-ray absorption spectroscopy was performed to characterize Mn-doped Bi 3.25 La 0.75 Ti 3 O1 2 (BLT) ceramics with various MnO 2 dopants. The x-ray absorption near-edge structure (XANES) was analyzed in combination with first principle calculation of Mn K-edge to identify atomic position of Mn in BLT. The result confirms Mn 4+ substituting on Ti 4+ -site in BLT. Further, the extended x-ray absorption fine structure (EXAFS) was examined where Mn K-edge of Mn-doped BLT was compared to that of Ti K-edge of BLT in R-space. The result shows radial distances between Mn 4+ and O 2- ions in ab-axis are almost equal and decrease with increasing Mn-doping contents. This is strong evidence that Mn 4+ substituting on Ti 4+ site can be reduced the orthorhombicity, which increase the polarization domains size and enhance remnant polarization, speed up the polarization domains movement and lessen coercive field. © 2013 Copyright Taylor and Francis Group, LLC.